The Expression of Toll-Like Receptor 4 mRNA in PBMCs Is Upregulated in Smokers and Decreases Upon Smoking Cessation - Yeh, Hsin-Yu; Hung, Shou-Hung; Chen, Su-Chiu; Guo, Fei-Ran; Huang, Hsien-Liang; Peng, Jen-Kuei; Lee, Chung-Sheng; Tsai, Jaw-Shiun (Frontiers in Immunology, 2021)
Background：Studies have shown in vitro that cigarette smoke condensate stimulates monocytes to express toll-like receptor 4 (TLR4), tumor necrosis factor-α (TNF-α), and intercellular adhesion molecule 1 (ICAM-1), and enhances their adhesion to the endothelium. However, the same effects of cigarette smoking have not been explored in vivo. This study is to investigate the effect of cigarette smoking and smoking cessation on their mRNA expression in human peripheral blood mononuclear cells (PBMCs). Methods：A group of 97 smokers and 62 nonsmokers were enrolled. The RNA from PBMCs was assessed with real-time polymerase chain reaction (PCR) to determine the levels of ICAM-1, TNF-α, and TLR4. The same markers in PBMCs of 87 quitters were examined before and at one week, one month, and two months after smoking cessation. Results： Of the 97 smokers, 85 (87.6%) were males, and 30 (48.4%) of the nonsmokers were males (p < 0.0001). The mean (SD) age of the smokers was 43.24 (10.89) years, which was younger than 43.45 (11.41) years of nonsmokers (p < 0.0001). The incidence of cardiovascular diseases was 13.4% in smokers, which was higher than 1.6% in nonsmokers (p < 0.05). Both ICAM-1 and TNF-α mRNA levels in PBMCs were higher among the smokers (p < 0.0001). In addition, TLR4 mRNA levels in PBMCs were statistically elevated in the smokers (p < 0.0001) comparing with those in the nonsmokers. The mRNA levels of TLR4 and TNF-α in PBMCs decreased in those who had quit smoking for 2 months (p < 0.0001). Conclusions：ICAM-1, TNF-α, and TLR4 mRNA expression levels in PBMCs increased in smokers and decreased after being on a smoking cessation program for 2 months. This finding suggested that TLR4 expression may mediate the atherogenic inflammatory process induced by smoking.